Lí thuyết hoạt động và bản sắc xã hội: Bài học kinh nghiệm của sinh viên Khoa tiếng Anh của Đại học Hà Nội /Phạm Thu Hằng. - Phạm, Thu Hằng.
Activity theory and social indentity theory have been coming to the fore of word linguistics research and academic discussion for a long time. They have proven to be useful tools for analyzing and theorizing about language classroom settings to help teachers understand more about their teaching and students. This paper attempts to throw some light on important research in activity theory, social indentity theory and their relation as well as attempts to create a link between these two theories to my teaching context in the English Department, Hanoi University of Vietnam.